THE EVOLUTION OF THE INTERFERENCE OF NEW TECHNOLOGIES IN MUSICAL CREATION - Ciprian Gabriel POP (Studia Universitatis Babeş-Bolyai. Musica)
The present study follows the new technologies adopted in musical creation and production. We diachronically pursued the first steps of technologies involving electronics in musical processes. We presented examples of devices and inventions with applicability in music, which stood the test of time. The diachronic perspective includes the present and, in the end, we highlighted the main direction of the present time: the virtualization of devices due to computers, hence, the enormous potential, very little exploited, of musical software in musical creation. The second part of the study presents specific examples from the author’s own works presented as case studies where new technologies help and renew musical creation.